Biomimetic interfacial assembly of CaCO3 microspheres using egg-white foam and their interaction with Sr2+. Issue 15 (15th October 2017) - Qiao, Zheng; Liu, Xun; Duan, Xiaohui; Zhou, Yong; Pei, Chonghua; Ma, Yongjun
Abstract: Since egg-white protein is an excellent amphoteric surfactant and an outstanding regulator of CaCO3 mineralization, we prepared an egg-white foam as the organic matrix and template to regulate mineralization of CaCO3 and assemble primary mineralization particles. Samples were characterized by scanning electron microscopy, powder X-ray diffraction, Fourier transform infrared spectroscopy and high-resolution transmission electron microscopy, showing that the particles are homogeneous (2 µm) vaterite spherules of CaCO3 . The results of the interaction between the particles and Sr 2+ show that Sr 2+ can induce transformation of the particles from vaterite to calcite and that it is simultaneously adsorbed by the particles, reaching 89.9% adsorption after 36 h.